KARAKTERISTIK IBU YANG MELAHIRKAN BAYI DENGAN BERAT BADAN LAHIR RENDAH (BBLR) DI RSU Dr. PIRNGADI MEDAN TAHUN 2012 SAMPAI 2013 - Erika Desi C. Pardede; dr.Rahayu Lubis, Mkes, P.hd; drh.Hiswani ,Mkes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Low birth weight infant is a newborn baby whose weight at birth less than 2500 gram. Low birth weight infant including major factor in the increased mortality, morbidity baby and children. The prevalence of low birth weight according to the World Health Organization (WHO) in 2010 estimated 15% of all births in the world with limits 3.3% -3.8% and is more common in developing countries or low socioeconomic. The prevalence of low birth weight infant in Indonesia 2013 amounted to 10.2%.To know the charecteristics of mother who delivered low birth weight infant at General Hospital dr. Pirngadi Medan in 2012-2013, The population and sample 100 mother who delivered low birth infant. a descriptive study has been done by using a case series design and continued with the statistical analysis. Socio-demographically, highest proportion, 20-35 years old (64,0%), High Educated (70,0%), Islam (80,0%), Housewife (68,0%), and labor cost of BPJS (95,0%), Medico Obstetric, highest proportion : Primipara (56,0%), Interval of pregnancies with first-born child (55,0%), and Hb level ≥11 gram % (80,0%), Condition of baby’s born alive (81,0%), average length of stay 15,3 days (15 days), home in a state of recovery (92,0%), there is a differences between Hb level and Low birth weight infant (p = 0,042), there is no significant differences between parity and Low birth weight infant (p = 0,174), there is no significant differences between interval of pregnancies and Low birth weight infant (p = 0,106), there is no significant differences between proportion of condition infant at birth and Low birth weight infant ( p= 0,780). Pregnant mother especially who at risk, expected to check up her pregnancy regularly and increasing balanced nutrition to prevent the birth of babies with low birth weight. To General Hospital Dr. Pirngadi Medan, expected to complete the data registration system in medical record such as, gestational age, ethnic group, and some obstetric history is not contained in the card status. Low birth weight infant is a newborn baby whose weight at birth less than 2500 gram. Low birth weight infant including major factor in the increased mortality, morbidity baby and children. The prevalence of low birth weight according to the World Health Organization (WHO) in 2010 estimated 15% of all births in the world with limits 3.3% -3.8% and is more common in developing countries or low socioeconomic. The prevalence of low birth weight infant in Indonesia 2013 amounted to 10.2%.To know the charecteristics of mother who delivered low birth weight infant at General Hospital dr. Pirngadi Medan in 2012-2013, The population and sample 100 mother who delivered low birth infant. a descriptive study has been done by using a case series design and continued with the statistical analysis. Socio-demographically, highest proportion, 20-35 years old (64,0%), High Educated (70,0%), Islam (80,0%), Housewife (68,0%), and labor cost of BPJS (95,0%), Medico Obstetric, highest proportion : Primipara (56,0%), Interval of pregnancies with first-born child (55,0%), and Hb level ≥11 gram % (80,0%), Condition of baby’s born alive (81,0%), average length of stay 15,3 days (15 days), home in a state of recovery (92,0%), there is a differences between Hb level and Low birth weight infant (p = 0,042), there is no significant differences between parity and Low birth weight infant (p = 0,174), there is no significant differences between interval of pregnancies and Low birth weight infant (p = 0,106), there is no significant differences between proportion of condition infant at birth and Low birth weight infant ( p= 0,780). Pregnant mother especially who at risk, expected to check up her pregnancy regularly and increasing balanced nutrition to prevent the birth of babies with low birth weight. To General Hospital Dr. Pirngadi Medan, expected to complete the data registration system in medical record such as, gestational age, ethnic group, and some obstetric history is not contained in the card status.